2015
DOI: 10.3389/fncel.2015.00410
|View full text |Cite
|
Sign up to set email alerts
|

Lysosomal and phagocytic activity is increased in astrocytes during disease progression in the SOD1 G93A mouse model of amyotrophic lateral sclerosis

Abstract: Astrocytes are key players in the progression of amyotrophic lateral sclerosis (ALS). Previously, gene expression profiling of astrocytes from the pre-symptomatic stage of the SOD1G93A model of ALS has revealed reduced lactate metabolism and altered trophic support. Here, we have performed microarray analysis of symptomatic and late-stage disease astrocytes isolated by laser capture microdissection (LCM) from the lumbar spinal cord of the SOD1G93A mouse to complete the picture of astrocyte behavior throughout … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 48 publications
0
36
0
Order By: Relevance
“…Interestingly, astrocytes have been previously suggested as important cellular targets in CNS motor disorders [87, 88], although specific molecular targets are not clear. In the context of Meth abuse, movement disorders are very common sequels and comorbidities [89].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, astrocytes have been previously suggested as important cellular targets in CNS motor disorders [87, 88], although specific molecular targets are not clear. In the context of Meth abuse, movement disorders are very common sequels and comorbidities [89].…”
Section: Discussionmentioning
confidence: 99%
“…An increasing number of studies in a range of neurological diseases have used this approach to identify disease-relevant, cell-specific gene expression changes (Boone et al, 2013, Chu et al, 2009, Kumar et al, 2013, Pietersen et al, 2009, Simpson et al, 2011, Baker et al, 2015. To date, only two studies have employed LCM in the investigation of human MS cases: one identifying gene expression changes in total extracts from NAWM, peri-lesional and lesional regions compared to control WM (Mycko et al, 2012) and the other identifying transcriptomic changes in the vascular compartment in MS (Cunnea et al, 2010); with neither study specifically assessing changes in the astrocyte transcriptome.…”
Section: Discussionmentioning
confidence: 99%
“…Astrocytes isolated from cortices at 0-2 day-old mSOD1 mice have previously exhibited enhanced reactivity [61], though those of mSOD1 rodents isolated from the SC of 1day-old pups revealed to express lower levels of S100B and Cx43, and more GLT-1, than those obtained from the adult SC of symptomatic animals [13]. Nevertheless, it was lately shown that astrocytes from the cerebral cortices of 7-8 day-old mice P301S tau transgenic mice possess an abnormal phenotype that is retained in adulthood, in contrast with those from 1 to 2 day-old mice, indicating that the astrocytic reaction can take some days to develop [62].…”
Section: Astrocytes Isolated From the Cortex Of Msod1 Mice Pups Exhibmentioning
confidence: 99%